PENGARUH MEDIA DAKOTA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA MATERI KPK DAN FPB MATA PELAJARAN MATEMATIKA KELAS IV SDN 01 GEMUHBLANTEN - Ardhia, Winda Putri; Prasetiyawati, Dwi; Baedowi, Sunan (Elementary School Teacher and Education (PGSD), Faculty of Teacher Training and Education, 2019)
The purpose of this study was to determine the effect of dakota media on students' critical thinking skills in KPK and FPB material. This type of research is quantitative with the research design of One-Group Pretest-Posttest Design. The population were all fourth grade students of SDN 01 Gemuhblanten. The sample taken was 19 fourth grade students. The data in this study were obtained through tests, interviews, observations, and documentation. The results of hypothesis testing on students' critical thinking abilities show that tcount 19.851 and ttable 2.086 with a significancy level of 5%. Because tcount> ttable is 19.851> 2.086, then Ha is accepted, that is, dacota media has an effect on students' critical thinking abilities.